2022
DOI: 10.3390/ijms232113577
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular and Cellular Strategies of Glioblastoma and Non-Small-Cell Lung Cancer Cells Conferring Radioresistance

Abstract: Ionizing radiation (IR) has been shown to play a crucial role in the treatment of glioblastoma (GBM; grade IV) and non-small-cell lung cancer (NSCLC). Nevertheless, recent studies have indicated that radiotherapy can offer only palliation owing to the radioresistance of GBM and NSCLC. Therefore, delineating the major radioresistance mechanisms may provide novel therapeutic approaches to sensitize these diseases to IR and improve patient outcomes. This review provides insights into the molecular and cellular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 593 publications
(741 reference statements)
1
11
0
Order By: Relevance
“…The contribution of hypoxia-driven mechanisms to GSC-mediated radioresistance, as discussed by Alhaddad et al [ 40 ] resonates with the findings of Hsieh et al [ 45 ] NADPH oxidase subunit 4, identified as a mediator of cycling hypoxia-promoted radiation resistance in glioblastoma multiforme, underscores the intricate relationship between the tumor microenvironment and resistance mechanisms. The role of hypoxia in shaping the GSC phenotype adds a layer of complexity to the design of targeted therapies, necessitating strategies that account for the dynamic nature of the tumor microenvironment[ 2 , 6 , 46 ].…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The contribution of hypoxia-driven mechanisms to GSC-mediated radioresistance, as discussed by Alhaddad et al [ 40 ] resonates with the findings of Hsieh et al [ 45 ] NADPH oxidase subunit 4, identified as a mediator of cycling hypoxia-promoted radiation resistance in glioblastoma multiforme, underscores the intricate relationship between the tumor microenvironment and resistance mechanisms. The role of hypoxia in shaping the GSC phenotype adds a layer of complexity to the design of targeted therapies, necessitating strategies that account for the dynamic nature of the tumor microenvironment[ 2 , 6 , 46 ].…”
Section: Discussionsupporting
confidence: 59%
“…Additionally, Yi et al [ 30 ] targeted CK1α to reduce resistance to TMZ and radiotherapy, emphasizing the intricate network of pathways involved in GSC-mediated resistance. The study by Alhaddad et al [ 40 ] delves into the role of autophagy induction in promoting M2-like macrophage polarization, thereby contributing to radioresistance[ 41 ]. This contrasts with Li et al [ 42 ] where PI3Kγ inhibition suppresses microglia/TAM accumulation in the glioma microenvironment by inhibiting autophagy, ultimately promoting an exceptional response to TMZ[ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCLC is highly sensitive to radiotherapy in the early stages of treatment, but radioresistance inevitably develops in a significant proportion of patients [ 32 , 33 ]. Cancer radioresistance is an intricate phenomenon that has attracted a lot of attention, and there are two main hypotheses to explain it [ 34 , 35 ]. First, tumor cells with both high and low sensitivity to radiation exist in tumors.…”
Section: Discussionmentioning
confidence: 99%